IMPROVING STUDENT GUIDANCE PROGRAMMES AT LATVIA ’ S INSTITUTIONS OF HIGHER EDUCATION - Šmitiņa, Agita (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2015)
The aim of this study is to outline possibilities to improve and develop the student guidance system at Latvia’s higher education institutions, linking these to the main principles of management sciences. Certain problems and weaknesses related to the existing student guidance and support system at Latvian universities have been analysed. The results of a research project aimed at determining the needs of students of guidance showed that the services are very much appreciated among them. The author of this paper offers a series of suggestions and recommendations as to improve student guidance and support services at Latvia’s institutions of higher education. With an eye toward improving these systems, the author proposes the implementation of systematic analysis of the student guidance system, as well as implementation of the results at the national, institutional and individual level.